Does a previous aortic endograft confer any protective effect during abdominal aortic aneurysm rupture? Systematic review and meta-analysis of comparative studies. (June 2020) - Galanakis, Nikolaos; Kontopodis, Nikolaos; Tavlas, Emmanouil; Tsetis, Dimitrios; Ioannou, Christos V
Objectives: Whether prior endovascular aneurysm repair confers a protective effect in patients with ruptured abdominal aortic aneurysm (rAAA) is not known. We aimed to systematically review and compare the outcomes of rAAA in patients with and without prior endovascular aneurysm repair. Methods: We performed a systematic review that conformed to the Preferred Reporting Items for Systematic Reviews and Meta-analysis. We selected studies comparing the outcomes in patients with rAAA after prior endovascular aneurysm repair (group 1) and those with de novo rAAAs (group 2). We conducted a proportion meta-analysis of perioperative mortality and obtained summary estimates of odds ratios (ORs) and 95% confidence intervals (CIs) using random-effects models. Results: We included four studies (retrospective observational studies) in quantitative synthesis reporting a total of 719 patients (group 1 (89) group 2 (630)). The perioperative mortality in groups 1 and 2 was 30.4% and 41%, respectively, and there was no statistical significant difference between the groups (OR 0.66, 95% CI 0.30–1.43, P  = 0.29, I 2 =58%). However, patients presenting with rAAA following previous endovascular aneurysm repair were more hemodynamically stable (OR 0.33, 95% CI 0.12–0.90, P  = 0.03, I 2 =74%). The choice between endovascular or open surgery treatment in group 1 did not affect the perioperative mortality (OR 1.12, 95% CI 0.41–3.04  P  = 0.82, I 2 =0%). Endoleak types I and III were the main causes of rAAA in group 1. Conclusions: Perioperative mortality was similar for rAAA either de novo or after prior endovascular aneurysm repair. However, ruptures in patients with prior endovascular aneurysm repair presented hemodynamically more stable.